Cell-free fetal DNA and pregnancy-related complications (Review) - SIFAKIS, STAVROS (Mol Med Rep, 2015)
Cell-free fetal DNA (cff-DNA) is a novel promising biomarker that has been applied in various aspects of obstetrical research, notably in prenatal diagnosis and complicated pregnancies. It is easily detected by semi-quantitative PCR for the SRY target gene. It is well recognized that the levels of circulating cff-DNA play a role in various complications of pregnancy. In this review, we explore the implications of the detection of cff-DNA in a range of pregnancy-related complications, such as preeclampsia, intrauterine growth restriction (IUGR), preterm labor, placenta previa and hyperemesis gravidarum. cff-DNA is released due to apoptotic mechanisms occurring on trophoblastic cells, although recent in vivo studies support the existence of additional mechanisms. The increase in the levels of cff-DNA can be used to predict pregnancy-related complications and has great value in the field of prenatal diagnosis and in common pregnancy-related complications, as it precedes the clinical symptoms of the disease. Gestational age is a factor that determines the elevation in cff-DNA levels in response to pathological conditions. In conclusion, the detection of cff-DNA levels has a number of valuable applications in prenatal screening; however, the detection of cff-DNA levels has not yet been applied in clinical practice for the diagnosis of pregnancy-related disorders. Thus, studies are focusing on unraveling the etiology of alterations in its levels under pathological conditions during pregnancy, in order to determine the potenial predictive and diagnostic applications of this biomarker.